Assessment of oxygen saturation in retinal vessels of normal subjects and diabetic patients with and without retinopathy using Flow Oximetry System - Ibrahim, Mohamed A.; Annam, Rachel E.; Sepah, Yasir J.; Luu, Long; Bittencourt, Millena G.; Jang, Hyun S.; Lemaillet, Paul; Munoz, Beatriz; Duncan, Donald D.; West, Sheila; Nguyen, Quan Dong; Ramella-Roman, Jessica C. (Quantitative Imaging in Medicine and Surgery; Vol 5, No 1 (February 01, 2015): Quantitative Imaging in Medicine and Surgery (Emerging Technologies in Biomedical Imaging), 2014)
Purpose: To assess oxygen saturation (StO2) in retinal vessels of normal subjects and diabetic patients with and without retinopathy using the modified version of the Flow Oximetry System (FOS) and a novel assessment software. Methods: The FOS and novel assessment software were used to determine StO2 levels in arteries and veins located between 1 and 2 mm from the margin of the optic disc and in the macular area. Results: Eighteen normal subjects, 15 diabetics without diabetic retinopathy (DM no DR), and 11 with non-proliferative diabetic retinopathy (NPDR) were included in final analysis. The mean (±SD) StO2 in retinal arteries was 96.9%±3.8% in normal subjects; 97.4%±3.7% in DM no DR; and 98.4%±2.0% in NPDR. The mean venous StO2 was 57.5%±6.8% in normal subjects; 57.4%±7.5% in DM no DR; and 51.8%±6.8% in NPDR. The mean arterial and venous StO2 across the three groups were not statistically different (P=0.498 and P=0.071, respectively). The arterio-venous differences between the three study groups, however, were found to be statistically significant (P=0.015). Pairwise comparisons have demonstrated significant differences when comparing the A-V difference in the NPDR group to either normal subjects (P=0.02) or diabetic patients without DR (P=0.04). Conclusions: The arterio-venous difference was greater, and statistically significant, in patients with NPDR when compared to normal subjects and to patients with diabetes and no retinopathy. The mean venous StO2 was lower, but not statistically significant, in NPDR compared with diabetics without retinopathy and with normal subjects.